Sci-fi representation and heritage: vertical city - horizontal layered links (Architecture Image Studies, 2021)
Here are shared the first steps of an exploratory approach to a personal subject of fascination. The relation of drawing with the city of yesterday and tomorrow (ideally built trough the participation of us all). It’s a vast and wild territory of knowledge, that can have many different directions of exploratory approach. Several references come to my (non specialised) mind as unavoidable: the influence of cinema in works of Fritz Lang (Metropolis) or cult movie Blade Runner (and concept designs by Syd Mead), but also with any doubt, Giovanni Battista Piranesi body of work, or the incredible Francisco de Hollanda Renascence personality that in 1571 envisioned the future of Lisbon (Da Fábrica que Falece à Cidade de Lisboa, Of the works that the city of Lisbon lacks).